Fundamentals of electron energy-loss spectroscopy. Issue 1 (January 2016) - Hofer, F; Schmidt, F P; Grogger, W; Kothleitner, G
Abstract: Electron energy-loss spectroscopy (EELS) is an analytical technique that is based on inelastic scattering of fast electrons in a thin specimen. In a transmission electron microscope (TEM) it can provide structural and chemical information about a specimen, even down to atomic resolution. This review provides an overview of the physical basis and new developments and applications of EELS in scanning transmission electron microscopy. Recent advances in elemental mapping, spectrum imaging of plasmonic structures and quantitative analysis of atomically resolved elemental maps are highlighted.